Uso do esteatito como componente de espumas de poliuretano flexível - Plínio César de Carvalho Pinto (2011)
This work was focused on the chemical and mineralogical characterization of a steatite rock sample from the Mostardas Mine, in Nova Lima, state of Minas Gerais, Brazil. Results showed that steatite sample is composed of approximately 65% w/w talc, 29% w/w clinochlore, 5% w/w amphibole (tremolite and actinolite) and 1% w/w ofiron oxides and pyroxene. As talc is a mineral filler commonly used in industry, steatite was used in various formulations of flexible polyurethane foams partially replacing the polyol reagent in order to lower costs and improve the mechanical properties of the polymer.The reactivity studies showed that the polymer does not interact with the surface of the mineral by covalent bonds; it interacts only weakly via van der Waals bonds. The images of scanning electron microscopy indicate a possible interaction between the polymer and talc. The composites steatite/flexible polyurethane showed an increase in comfort factorand in the compressive strength of the foam, it compared to conventional flexible polyurethane foams, indicating an increase in load support and in comfort, provided by the composites. The chemical composition and thermal behavior of the foams were not significantly affected by steatite addition in polymer.